Recent Advances: Decoding Alzheimer’s Disease With Stem Cells - Fang, Yi; Gao, Ting; Zhang, Baorong; Pu, Jiali (Frontiers in Aging Neuroscience, 2018)
Alzheimer’s disease (AD) is an irreversible neurodegenerative disorder that destroys cognitive functions. Recently, a number of high-profile clinical trials based on the amyloid cascade hypothesis have encountered disappointing results. The failure of these trials indicates the necessity for novel therapeutic strategies and disease models. In this review, we will describe how recent advances in stem cell technology have shed light on a novel treatment strategy and revolutionized the mechanistic investigation of AD pathogenesis. Current advances in promoting endogenous neurogenesis and transplanting exogenous stem cells from both bench research and clinical translation perspectives will be thoroughly summarized. In addition, reprogramming technology-based disease modeling, which has shown improved efficacy in recapitulating pathological features in human patients, will be discussed.